Office-Based Procedure Training in Laryngology Fellowship Programs - ENVER, NECATİ (WILEY, 2021)
Objective To assess the current practices and challenges of training office-based procedures to laryngology fellows in the United States. Methods An anonymous web-based survey study was distributed to laryngology fellowship program directors, as listed by the American Laryngological Association. The survey was a 19-item questionnaire with free-text, Likert scale, and multiple-choice answers. Results Twenty-two of 27 program directors (81.4%) replied to the survey. Many programs (8/16) have three or more laryngologists and do more than 10 procedures each week (10/16). Sixty-nine percent (11/16) of directors had not been trained for office procedures in their fellowship. The fellows are allowed to be primary surgeon on 68.75% and 75% of vocal fold augmentation and laser procedures, respectively. The expected competencies for these procedures on graduation are average-moderate and moderate. When program directors asked about the methods used for training, a minority of them use simulators (2/16), procedural checklists (2/16), or structured debriefing (2/16). The most commonly used methods were case-based troubleshooting (13/16) and unstructured debriefing (13/16). Patients being awake and patients' expectations are seen as the most important obstacles. Most of the directors thought office-based procedure training could be improved (14/16). The most common suggestions were using step-wise checklists, simulator-labs, and formal debriefings. Conclusion This is the first study evaluating the training of office-based laryngeal procedures during laryngology fellowship. Given the increasing importance of these procedures in practice and the herein identified barriers and need for improvement, fellowships should investigate the use of systematic training tools to improve fellow competency with office-based procedures.Laryngoscope, 2020
Keywords: Fellowship; laryngology; office-based laser surgery; office-based procedures; vocal fold Injection; office surgery; KTP laser; LASER-SURGERY; COST; VALIDATION; SIMULATION